Filsafat Ishrāqiyyah (Iluminatif) Suhrawardī al-Maqtūl - Ahmad Hasan Ridwan (Al-Jami'ah: Journal of Islamic Studies, 1998)
The Ishrāqī is oriental as well as illuminative philosophy. It is to shine, for it comes from the Orient; and it is oriental, because it shines. Colored with its distinct language, this philosophy constitutes an alliance between the "speculative" philosophy (al-ḥikmah al-baḥthiyyah) which is a fusion of the Hellenistic, Persian and Islamic philosophy, and the "intuitive" one (al-ḥikmah al-dhawqiyyah) that represents mystical spiritualism and is a combination of the Islamic sūfi tradition, Zoroastrianism and Neo-Platonism. Shuhrawardī, who was accustomed with perennial Islamic philosophy (al-ḥikmah al-'atīqah), is considered not only as a great mystic, but also an Ishrāqī philosopher. His Ishrāqī thought is a synthesis of several philosophical notions which eventuated in the classical Islam. His ideas are recognized as a set of universal teachings, which is a long-lasting oriental thought and has actual significance for the modern period.